Phenotypic detection and incidence of inducible clindamycin resistance among Staphylococcus aureus from tertiary care hospital - Sande (Tathe), Suvarna Vaibhav (International Journal of Advances in Medicine, 2017)
Background: Among few therapeutic alternatives available for treatment of erythromycin resistant Staphylococcus aureus infections, clindamycin has several advantages but major barrier in its usage is development of resistance especially inducible resistance due to erm genes resulting in treatment failure. In vitro routine tests for clindamycin susceptibility may fail to detect such resistance which can be detected by simple D test. Hence the present study was undertaken to detect incidence of inducible resistance to clindamycin in erythromycin resistant S. aureus isolates by D test and to study the relationship between clindamycin and methicillin resistance. Methods: 330 S. aureus isolates were subjected to routine antimicrobial susceptibility test by Kirby-Bauer’s disc diffusion method using various antimicrobial agents. Erythromycin resistant isolates were studied for detection of inducible and constitutive clindamycin resistance by D test according to CLSI guidelines. Results: Out of 152 erythromycin resistant S. aureus, 46 (30.2%) isolates showed inducible clindamycin resistance, 54 (35.5%) showed constitutive resistance while 52 (34.2%) showed MS phenotype. The percentage of inducible and constitutive resistance was more among MRSA (33.3% and 46.6%) than MSSA (25% and 19.3%) while the percentage of MS phenotype was more among MSSA (54.8%) than MRSA (20%). Conclusions: D test should be used in routine disc diffusion testing for the detection of inducible clindamycin resistance for the proper treatment of the patient.